3D flexible Si based-composite (Si@Si3N4)/CNF electrode with enhanced cyclability and high rate capability for lithium-ion batteries. (September 2016) - Kim, Si-Jin; Kim, Min-Cheol; Han, Sang-Beom; Lee, Gyu-Ho; Choe, Hui-Seon; Kwak, Da-Hee; Choi, Sun-Yong; Son, Byung-Goo; Shin, Myoung-Sun; Park, Kyung-Won
Abstract: Despite extremely high capacity of Si-based anodes in lithium-ion batteries (LIB), Si-based materials have shown a structural collapse caused by a volumetric expansion/contraction during the cycling process. The conventional electrode structure, which consists of active materials, a current collector, a conducting agent, and a binder, actually showed a low loading of active material due to the other heavy components. In this study, we prepared a 3D flexible Si-composite electrode consisting of core (Si)-shell (Si3 N4 ) NPs (Si@Si3 N4 ) and carbon nanofibers (denoted as Si-composite/CNF). The Si-composite/CNF was directly utilized as an anode in the absence of the other components was electrochemically evaluated using a coin-type cell. The Si-composite/CNF showed a high capacity of 665 m Ah g −1 at a fairly high current density of 10 A g −1 and an extremely low capacity loss for 2000 cycles. Graphical abstract: Highlights: We prepared Si-composite/CNF exhibits a 3D flexible Si-composite electrode. The electrode consists of core (Si)-shell (Si3 N4 ) NPs (Si@Si3 N4 ) and carbon nanofibers. The Si-composite/CNF was directly utilized as an anode. Si-composite /CNF exhibited high specific capacity and improved high rate cycling performance.